Facile strategy to improve thermal conductivity of anisotropic poly(butylene succinate) phosphorus‐containing ionomer films via compression molding. (16th November 2020) - Ru, Ke; Chen, Anfu; Jiang, Guo; Zhang, Shuidong
Abstract : One of the defect for polymers based film is the low thermal conductivity which restricts their application. In this study, an effective strategy in improving the thermal conductivity of poly(butylene succinate) phosphorus‐containing ionomer [phosphorus‐containing ionic group (PCIG) content was 1wt%, denoted as PBSI1‐K] by compression molding was proposed. PBSI1‐K films with anisotropic thermal transport were fabricated by thermal compression molding with different compression molding pressure (2000, 2500, 3000, and 3500 psi). The relationships between the compression molding pressure and properties, including thermal conductivity, crystallization behavior and chain orientation degree of PBSI1‐K films were investigated. Strikingly, PBSI1‐K film fabricated at 2500 psi pressure, denoted as PBSI1‐K‐2500, achieved 5‐fold increase in in‐plane thermal conductivity when PBS was used as the contrast. The impressive improved thermal conductivity (542 mW m −1 K −1 ) in horizontal direction are ascribed to the fact that PBSI1‐K‐2500 obtained the large spherulite diameter (517 um) and high chain orientation degree (1.90). Furthermore, we introduced graphene into PBSI1‐K and the thermal conductivity of GNS/PBSI1‐K composites have also been discussed. We hence showcase compression molding here as a facile strategy to prepare ionomer film with improved thermal conductivity. The prepared PBSI1‐K‐2500 can serve as biodegradable films to replace petroleum‐based plastic materials and remedy the pollution of "microplastics."